2018
DOI: 10.1111/iwj.12968
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Hawthorne effect in wound research—A scoping review

Abstract: The Hawthorne Effect (HE) is considered a methodological artefact in research, although its definition and influence on research outcomes lack consensus. This review explored how this term has been mentioned and discussed in the area of wound research. A scoping review was conducted on ProQuest Central, Scopus, EbscoHost, and online databases of indexed wound journals using the methodological framework by Arksey and Malley. A review protocol was applied to detail key terms, truncation and Boolean operators, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 55 publications
0
18
0
1
Order By: Relevance
“…This highlights what has been reported in the reviews by McCambridge and Nguyen et al . about the incorrect use of the Hawthorne as justification for unexpected results . The remaining four studies have used the Hawthorne effect as an explanation for improved outcomes reported by the patients (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This highlights what has been reported in the reviews by McCambridge and Nguyen et al . about the incorrect use of the Hawthorne as justification for unexpected results . The remaining four studies have used the Hawthorne effect as an explanation for improved outcomes reported by the patients (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…have noted, there is potential for research participation bias to occur in a study due to the interaction of the participation effect on the intervention and this form of bias will not be eliminated completely by randomization . A proposed study design to overcome research participation bias is the Solomon four‐group design, with assessed and unassessed, hence unaware of the study, control and intervention groups …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations